Evaluation of Islamic Education Assessment Instruments for Differentiated Learning - Savana, Oseolla; Sutiyono, Agus (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2025)
Implementation of the Merdeka curriculum emphasizes learning that adapts to students' needs, interests, and readiness. However, in practice, assessment in Islamic Religious Education (PAI) subjects still tends to be uniform and does not reflect the principle of differentiation. Subjects still tend to be uniform and do not reflect the principle of differentiation. This study aims to analyze the suitability of PAI assessment instruments with the principle of differentiated learning. Principle of differentiated learning. Using a descriptive qualitative approach, data were collected through interviews with PAI teachers in junior and senior high schools. Data analysis was conducted through reduction, presentation, and conclusion drawing. The results showed that most teachers had not developed an assessment that paid attention to individual student variations. The main obstacle is the lack of teachers' understanding of differentiated assessment and limited training. Conclusions indicate the need for teacher capacity building, policy support, and integration of differentiation principles in lesson planning and evaluation.